User Decision Factors in Financial Apps: Application Features, Utility, and Risk Analysis - Indriani Candra Kartika; Rita Ambarwati (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine the role of application features, utilitarian benefits, and the level of risk in influencing usage decisions in users of the funds application. This study uses a causal quantitative approach with the population being users of the funds application. This research was conducted using probability sampling method with simple random sampling technique. The data consists of primary data with 138 respondents. Data collection techniques by distributing questionnaires and answers will be measured on a Likert scale. The data analysis technique uses the PLS-SEM method with the help of SmartPLS software version 3.0. The results of this study indicate that application features, utilitarian benefits, and risk levels have a positive and significant effect on the decision to use the fund application. The implication of this research is to increase company awareness in optimising the existing infrastructure in the funds application, so as to increase the convenience of users of the funds application.